2020
DOI: 10.1007/s10592-020-01282-6
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the geographic origin of Spanish Cedar (Cedrela odorata L.) based on DNA variation

Abstract: The legality of wood products often depends on their origin, creating a need for forensic tools that verify claims of provenance for wood products. The neotropical tree species Cedrela odorata (Spanish cedar) is economically valuable for its wood and faces threats of overexploitation. We developed a 140 SNP assay for geographic localization of C. odorata specimens. Target capture and short-read sequencing of 46 C. odorata specimens allowed us to identify 140 spatially informative SNPs that differentiate C. odo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 85 publications
1
13
0
Order By: Relevance
“…As for the DNA stock concentration, the call rate (CR) seemed to be surprisingly little affected by time since collection when comparing modern with historical samples (Figure 2b ); our historical samples obtained a consistently high CR (mean = 99.71%, min = 95.65%, and max = 100%), which was approximately equal to that of the modern samples (mean = 99.89%, min = 94.57%, and max = 100%). In addition, historical materials of both animals and plants have been successfully genotyped using microfluidic SNP arrays (e.g., Finch et al, 2020 ; Johnston et al, 2013 ; Östergren et al, 2021 ). Compared with our results, however, these authors found much higher differences in the CR between historical and modern samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the DNA stock concentration, the call rate (CR) seemed to be surprisingly little affected by time since collection when comparing modern with historical samples (Figure 2b ); our historical samples obtained a consistently high CR (mean = 99.71%, min = 95.65%, and max = 100%), which was approximately equal to that of the modern samples (mean = 99.89%, min = 94.57%, and max = 100%). In addition, historical materials of both animals and plants have been successfully genotyped using microfluidic SNP arrays (e.g., Finch et al, 2020 ; Johnston et al, 2013 ; Östergren et al, 2021 ). Compared with our results, however, these authors found much higher differences in the CR between historical and modern samples.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we add a historic level to the species monitoring of the flowering plant species, Dracocephalum ruyschiana L. (northern dragonhead; Lamiaceae) by testing a microfluidic‐based SNP genotyping array on old herbarium specimens. This approach has recently been applied by others to historical materials of, for example, tropical tree species and salmon (Finch et al, 2020 ; Johnston et al, 2013 ; Östergren et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many genetic approaches have been used to verify the origin and trade routes of protected wildlife species, including elephant ivory (Wasser et al 2004), sturgeon and paddlefish caviar (Ogden et al 2013), tigers (Kitpipit et al 2012), birds (Abe et al 2012), and fishes (Clemento et al 2014). Several marker sets have been developed and tested in plants, namely Gonystylus (Ogden et al 2008), Intsia (Lowe et al 2017), Swietenia (Degen et al 2013), Larix (Blanc-Jolivet et al 2018, and Cedrela (Finch et al 2020;Paredes-Villanueva et al 2020). Lowe and Cross (2011) reported that DNA technology can be broadly applied to trace the origin of timber (Figure 7), and analysis methods continue to become available and improved (Degen et al 2013).…”
Section: Dna Analysismentioning
confidence: 99%
“…The legality of wood products usually depends on their source 18 . SSR is also often used in genetic diversity and population structure analysis of species 14 , 19 , and can further predict species' geographic provenance and distribution.…”
Section: Introductionmentioning
confidence: 99%